Tanshinone IIA attenuates TNF-α induced PTX3 expression and monocyte adhesion to endothelial cells through the p38/NF-κB pathway. (November 2018) - Fang, Jian; Chen, Qiuyan; He, Baozhu; Cai, Jiaxuan; Yao, Yawen; Cai, Yi; Xu, Suowen; Rengasamy, Kannan R.R.; Gowrishankar, Shanmugaraj; Pandian, Shunmugiah Karutha; Cao, Tiansheng
Abstract: Tanshinone IIA is one of the most predominant bioactive constituents of Danshen, a traditional Chinese medicinal plant with multiple cardiovascular protective actions. Although Tanshinone IIA has been well documented for its endothelial protective efficacy, studies unveiling the mechanism and/or molecular targets for its pharmacological activity are still inadequate. In recent studies, it has been envisaged that the expression of pentraxin 3 (PTX3) was associated with atherosclerotic cardiovascular diseases (ACVD). Therefore, the current study was designed to evaluate the possible role of Tanshinone IIA in influencing the expression of PTX3 in endothelial cells and thereby prevents endothelial dysfunction. Molecular analyses through real-time PCR, western blot, and ELISA revealed that Tanshinone IIA down-regulates PTX3 gene expression as well as protein secretion in human endothelial cells in the presence or absence of TNF-α. Besides, Tanshinone IIA inhibits the adhesion of THP1 cells (a monocytic cell line) to activated-endothelial cells stimulated with TNF-α. Furthermore, mechanistic studies uncovered the role of p38 MAPK/NF-κB pathway in Tanshinone II-A mediated pharmacological effects. Thus, the present study exemplifies the manifestation of Tanshinone IIA as a plausible alternative natural remedy for ACVD by targeting PTX3. Highlights: Pentraxin 3 (PTX3) promotes endothelial inflammation and monocyte adhesion. Tanshinone IIA is a natural PTX3 inhibitor that ameliorates monocyte adhesion. Tanshinone IIA reduces PTX3 expression via p38 MAPK/NF-kB pathway.